Atlantic meridional overturning circulation modulation of late Pleistocene to middle Holocene Asian summer monsoon variability and palaeoanthropological implications. Issue 1 (15th September 2021) - Li, Xinxia; Xiao, Guoqiao; Lin, Shan; Qiang, Xiaoke; Ao, Hong
Abstract: Asia contains more than half the world's population, and their lives are significantly related to summer monsoon moisture supply. Here, we investigate features and dynamics of late Pleistocene–middle Holocene Asian summer monsoon variability in the Nihewan Basin, North China, which was a critical home for early humans in East Asia throughout the Quaternary. We present new mineral magnetic records between ∼16 and 6 ka from the Yujiagou archeological site in the northern Nihewan Basin, which contains >40 000 stone tools, 2 pottery pieces and 19 686 mammal fossils. Magnetic properties of the Yujiagou section are dominated by pedogenic fine-grained magnetite/maghemite concentration, which ranges from superparamagnetic/single domain up to fine pseudo-single domain sizes. We use multiple environmental magnetic proxies, which measure pedogenic magnetite/maghemite concentration, to document that summer monsoon precipitation was low before ∼14.5 ka and high during the Bölling–Allerød warm period (14.5–12.8 ka), and shifted to low values at the onset of the Young Dryas cold period ∼12.4 ka, followed by a sustained long-term increasing trend from 12.4 to 6 ka. We relate these monsoon precipitation changes to the consistent Atlantic Meridional Overturning Circulation variability, which modulated North Hemisphere temperatures and displacements of Inter-Tropical Convergence Zone and Walker circulation over the Pacific Ocean. The observed large-amplitude deglacial Asian monsoon changes may have played a role in several key evolutionary changes in Asia implicated by the Yujiagou archeological evidence, including Paleolithic to Neolithic culture transition, Asian pottery development, and early human dispersals from Asia to America.